A Discourse Historical Approach on Local Wisdom in Amanat Galunggung Manuscript: Applying Discursive Strategy - Yatmikasari, Ika; Isana, Widiati (ASPENSI in Bandung, Indonesia, 2017)
ABSTRACT: Civilized society is those who appreciate and maintain their heritage which is, then, manifested into a set of local wisdom. Local wisdom is an activity containing way of life and knowledge undertaken by local people to answer problems in fulfilling their necessity. The socio-cultural condition of Sundanese people at the time âAmanat Galunggungâ (Message of Galunggung) was produced, which include religious, socio-economic, and cultural conditions, is precisely captured by the text. Through its discursive strategies, the text presents that the religious life of Sundanese people at that time is mostly influenced by Hinduism. In economic side, people of Sunda generally work in farming field. Meanwhile, the cultural condition indicates the pluralistic life of Sundanese community. The present researchâs effort is to examine the representation of Sundanese local wisdom in an old text entitled âAmanat Galunggungâ which was written in 16th century. Framed generally by CDA (Critical Discourse Analysis) theory and method, and particularly DHA (Discourse Historical Approach), the examination is focused on observing the five discursive strategies in micro-analysis under DHA, which includes strategies of nomination, predication, argumentation, perspectivation, and mitigation. The discussion also highlights the socio-cultural background of Sundanese people in that period to see its influence on the content of the text itself. Thus, the integration of two disciplinaries of historical study and linguistics is well-achieved. KEY WORDS: Local Wisdom; Socio-Cultural Background; Discursive Strategies; Manuscript of Amanat Galunggung; Sundanese Society.Â Â About the Authors: Ika Yatmikasari and Widiati Isana are the Lecturers at the Faculty of Adab and Humanities UIN SGD (State Islamic University, Sunan Gunung Djati) Bandung, Jalan A.H. Nasution No.105, Cipadung, Bandung 40614, West Java, Indonesia. For academic interests, the authors are able to be contacted via e-mails at: ikayatmikasari@gmail.com and widiatiisana@gmail.comRecommended Citation: Yatmikasari, Ika & Widiati Isana. (2017). âA Discourse Historical Approach on Local Wisdom in Amanat Galunggung Manuscript: Applying Discursive Strategyâ in TAWARIKH: International Journal for Historical Studies, Vol.9(1), October, pp.1-8. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980.Article Timeline: Accepted (August 5, 2017); Revised (September 8, 2017); and Published (October 28, 2017).